A novel high-yield synthesis of aminoacyl p-nitroanilines and aminoacyl 7-amino-4-methylcoumarins: Important synthons for the synthesis of chromogenic/fluorogenic protease substrates - Wu, Xinghua; Chen, Yu; Aloysius, Herve; Hu, Longqin (Beilstein Journal of Organic Chemistry, 2011)
Aminoacyl p-nitroaniline (aminoacyl-pNA) and aminoacyl 7-amino-4-methylcoumarin (aminoacyl-AMC) are important synthons for the synthesis of chromogenic/fluorogenic protease substrates. A new efficient method was developed to synthesize aminoacyl-pNA and aminoacyl-AMC derivatives in excellent yields starting from either amino acids or their corresponding commercially available N-hydroxysuccinimide esters. The method involved the in situ formation of selenocarboxylate intermediate of protected amino acids and the subsequent non-nucleophilic amidation with an azide. Common protecting groups used in amino acid/peptide chemistry were all well-tolerated. The method was also successfully applied to the synthesis of a dipeptide conjugate, indicating that the methodology is applicable to the synthesis of chromogenic substrates containing short peptides. The method has general applicability to the synthesis of chromogenic and fluorogenic peptide substrates and represents a convenient and high-yield synthesis of Nα-protected-aminoacyl-pNAs/AMCs, providing easy access to these important synthons for the construction of chromogenic/fluorogenic protease substrates through fragment condensation or stepwise elongation.
Keywords: 7-amino-4-methylcoumarin; p-nitroaniline; proteolytic substrate; selenocarboxylate/azide amidation; synthon